KEBERAGAMAN DALAM KESATUAN: BHINNEKA TUNGGAL IKA SEBAGAI PILAR PEMBENTUKAN HUKUM NASIONAL DI REPUBLIK INDONESIA - Yulianus Payzon Aituru; Maria Yeti Andrias (LPPM Universitas Ekasakti Padang, 2023)
This article delves into the role of the Bhinneka Tunggal Ika concept in shaping the national legal framework of the Republic of Indonesia. Within the context of diversity that characterizes the nation, Bhinneka Tunggal Ika is elevated as the central pillar coloring the legal formation process. The analysis involves a review of the values of diversity, unity, and oneness embedded in this concept, as well as how it is implemented in the national legal foundation. The aim of this article is to provide a profound understanding of how Bhinneka Tunggal Ika serves not only as a national motto but also as a philosophical basis inspiring the creation of an inclusive legal framework capable of responding to the dynamics of the heterogeneous Indonesian society. Through this analysis, it is expected that this article will contribute to a richer understanding of the relationship between Bhinneka Tunggal Ika and the sustainable formation of the national legal system in the Republic of Indonesia.